Sosialisasi Pemantauan Pertumbuhan dan Perkembangan Anak dengan Menggunakan KPSP pada Org Tua - Miniharianti; Hijriana, Isni; Wahidanur; Sari, Nadia; Nadia; Zahara, Zulfa (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2023)
Stimulating the growth and development of toddlers is a very important thing given by parents. If stimulation is inadequate, the growth and development of toddlers will be disrupted. However, in reality there are still many parents who do not understand the importance of screening and stimulating growth and development in children. Screening is carried out to detect irregularities early so that it will be easier to overcome them. One of the efforts to overcome this is by educating parents about stimulating growth and development using the KPSP format. KPSP is a tool/instrument used to determine whether a child's development is normal or whether there are deviations. The aim of this community service is to socialize monitoring of children's growth and development using KPSP among parents. The method used in this community service activity is active and participatory learning through several stages, namely the preparation stage, implementation stage and evaluation stage with a total of 20 parents participating. The results obtained were an increase in parental knowledge, in this case mothers, after being given education about monitoring children's growth and development using the Pre-Developmental Screening Questionnaire (KPSP). It is recommended that health workers need follow-up action from the Community Health Center so that they can facilitate supporting facilities for parents to independently screen their child's development.